IFLA, Moscow 1991: A personal perspective - Khoo, S.M. (Perpustakaan Universiti Malaya, 1991)
IFLA 1991 was an unforgettable experience, coinciding as it did with the attempted coup against the Soviet government. The article describes some experiences and observations, personal and professional, over the two week period of the Pre-Session Seminar and the General Conference.